Convolutional neural network model for synchrotron radiation imaging datasets to automatically detect interfacial microstructure: An in situ process monitoring tool during solar PV ribbon fabrication. (August 2021) - Kunwar, Anil; Malla, Prafulla Bahadur; Sun, Junhao; Qu, Lin; Ma, Haitao
Graphical abstract: Highlights: A data-driven approach using synchrotron radiation imaging experiments to explore the materials interface of PV ribbon. Morphological gradient operation identified as suitable data augmentation technique. Data of augmented images visualized with PCA technique. Bubble(s) and IMC identifying machine learning model developed using CNN. Abstract: Designing means and methods to detect the presence of interfacial bubbles and intermetallic compounds (IMCs) during hot dipping solder coating of Cu ribbon, can help in the production of defect-free PV ribbons. A mechanistic study of Cu 6 Sn 5 IMC grain growth and bubble morphology evolution at the solder-substrate interface is performed with phase field simulation. A machine learning model is utilized to identify the occurrence of bubble(s) and IMC at the material interface of liquid solder and solid Cu. The datasets for the microstructural images consisting of bubble(s), IMC and planar solder/Cu interface are generated using in situ synchrotron radiation (SR) imaging experiment techniques. The integration of in situ SR radiography based non-destructive testing experiments with convolutional neural network model to intelligently detect the interfacial microstructures paves the path for potential industrial application of this technique in the smart manufacturing of defect free and reliable PV ribbon material.